A high carbohydrate-fat free diet alters the proportion of heparin-bound VLDL in plasma and the expression of VLDL-ApoB-100 epitopes - Keidar, S. (Washington University School of Medicine, St. Louis, MO); Goldberg, A.C; Cook, K; Bateman, J; Schonfeld, G (Metabolism, clinical and experimental, 1990)
High carbohydrate-fat free diets (CHO-diet) induce the secretion of increased numbers of very-low-density lipoprotein (VLDL) particles and alter the composition and metabolism of VLDL. The aims of this study were to examine VLDL in greater detail, specifically to document any CHO-diet-induced alterations of apolipoprotein B-100 (apoB-100) epitope expression of VLDL, and any changes induced in subclasses of VLDL, as defined by heparin Sepharose chromatography. Fifteen normolipidemic subjects participated in the study by eating a basal typical American diet for 7 days and high carbohydrate diet (85% carbohydrate, less than 1% fat) for another 7 days. The sequence was changed in seven subjects. Fasting blood samples were analyzed for lipoprotein lipid and apoprotein concentrations. Heparin affinity VLDL subclasses were characterized chemically and electrophoretically [sodium dodecylsulfate-polyacrylamide gel electrophoresis (SDS-PAGE)]. Immunoreactivities of apoB in VLDL were tested in solid phase competitive-binding radioimmunoassays (RIAs) using five monoclonal anti-B antibodies that react with defined epitopes of apoB-100. The CHO diet produced consistent increases of plasma triglycerides in all subjects by a mean of 66% and decreases in plasma cholesterol by 18%. ApoB in plasma decreased by 21% and apoA-I by 17%; however, apoE and ApoA-II did not change. VLDL was enriched with triglycerides (55.0% +/- 0.8 v 57.0% +/- 0.7, P less than .05) and apoE (3.7% +/- 0.5 to 5.9% +/- 0.7, P less than .007) and the ratio between apoE and apoC in VLDL increased (0.15 +/- 0.03 to 0.25 +/- 0.03, P less than .002).